MAQĀṢID SHARI’AH DAN IMPLIKASINYA TERHADAP TAFSIR MAQĀṢIDĪ - Azzah Riscilia, Safira; Nikma, Sofiatun; Nysya' Uljannah, Salsa (MAQASHID Jurnal Hukum Islam, 2023)
The aim of this research is to find out the genealogy of Maqāṣid al-Shari‘ah and Tafsir Maqāṣidī, the urgency of Maqāṣid al-Shari‘ah in an interpretation, and the application of the interpretation of Maqāṣid al-Shari‘ah in Tafsir Maqāṣidī. In this case, the method used to find out some of the points above is using a qualitative method based on library research or by collecting reading sources which can be books, articles or journals related to the relevant sub-chapters. As for applying the verse, you need to know the legal basis by reading the verse through the lens of Maqāṣid al-Shari‘ah. From the research results, it can be seen that maqāshidi interpretation cannot be separated from Maqāṣid al-Shari‘ah because the two are interconnected with each other. And the importance of knowing the Maqāṣid al-Shari‘ah is to be able to reach the meaning beyond what the text says. Therefore, this research tries to bridge researchers to find out the genealogy, urgency and application of interpretation.